Giant vortex in a harmonically-trapped rotating dipolar 164Dy condensate - Young-S., Luis E.; Adhikari, S. K. [UNESP] (Elsevier, 2025)
We demonstrate the formation of dynamically stable giant vortices in a harmonically-trapped strongly dipolar 164Dy Bose–Einstein condensate under rotation around the polarization direction of dipolar atoms, employing the numerical solution of an improved mean-field model including a Lee-Huang-Yang-type interaction, meant to stop a collapse at high atom density. These giant vortices are stationary, obtainable by imaginary-time propagation using a Gaussian initial state, while the appropriate phase of the giant vortex is imprinted on the initial wave function. The dynamical stability of the giant vortices is established by real-time propagation during a long interval of time after a small change of a parameter.
Keywords: Bose-Einstein condensation; Dipolar interaction; Giant vortex; numerical analysis; Vortex formation